(untitled) (Journal of the Bangladesh Agricultural University, 2010)
This study was attempted to measure and compare resource use efficiency and relative productivity of farming under different tenure conditions in an area of Bhola district. A random sampling technique was used in the study. Sample farmers were classified as owner, crop share tenant and cash tenant farmers. A total of 90 samples, 30 from each class were selected on the basis of random sampling technique. The study explored the difference in the efficiency and productivity among owner, cash tenant and crop share tenant. Total cash expenses as well as total gross costs for producing HYV Boro rice was highest in owner farms and lowest in crop share tenant’s farm. When individual inputs were concerned it was observed that expenses on human labor shared a major portion of expenses in the production of HYV Boro rice where owner operators used more hired labor in compare to other groups. However, the cash tenant farmers were more efficient than owner and crop share tenant farmers. Due to poor resource base the crop share tenants were unable to invest on modern farm inputs. It may be mentioned that in Bangladesh the predominant tenancy arrangement is share cropping, which is an inefficient form of tenure arrangement in compare to cash tenancy. Keywords: Land tenure; Profitability; Efficiency; Elasticity of production DOI: 10.3329/jbau.v7i2.4730 J. Bangladesh Agril. Univ. 7(2): 247-252, 2009